Pro iOS Geo Building Apps with Location Based Services - Andreucci, Giacomo (Apress : Imprint: Apress, 2013)
Deepen your app development skills with Pro iOS Geo. This book shows you how to use geolocation-based tools to enhance the iOS apps you develop. Author Giacomo Andreucci describes different ways to integrate geo services, depending on the kind of app you're looking to develop: a web app, a hybrid app, or a native app. You'll discover how to use the Google Maps API features to integrate powerful geo capabilities in your apps with a little effort. You'll learn how to: Design geographic features for your apps while respecting usability criteria Design touristic geo apps Use HTML5 and the Google Maps JavaScript API to implement powerful geo functions in your apps Use Google Fusion Tables to display and query data in your maps Transform your geo web apps into hybrid apps that can be submitted to the Apple App Store Create native iOS geo apps using the new Apple Maps data through the Map Kit API After reading Pro iOS Geo, you'll have the knowledge and skills you need to add a geo dimension to all your apps, whether as a feature of a larger app- such as a social networking app that shows where friends are located in a selected area-or as the primary part of an app-such as a guide app that shows the monuments in your city. .